2009
DOI: 10.3354/meps08144
|View full text |Cite
|
Sign up to set email alerts
|

Steller sea lion foraging response to seasonal changes in prey availability

Abstract: We hypothesized that: (1) Steller sea lion Eumetopias jubatus diet choice is a function of prey availability, (2) sea lions move to take advantage of times and locations of seasonal prey concentrations and (3) the number present depends on the amount of prey available (numerical response). Over 3 yr, typically on a quarterly basis, in Frederick Sound, SE Alaska, multiple measurements were taken of Steller sea lion abundance (aerial surveys), diet (scats), dive behavior (satellite telemetry) and prey availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 70 publications
(108 reference statements)
7
87
0
Order By: Relevance
“…Sea lions change their diet based on seasonally and locally abundant prey and may migrate in response to seasonal prey fluctuations (Sigler et al 2009). The diets of both Steller and California sea lions, composed of a variety of bony and cartilaginous fishes and cephalopods, are often dominated by only a few species (Sinclair & Zeppelin 2002, Orr et al 2011, although as many as 25 different prey items have been found in a single scat (Riemer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sea lions change their diet based on seasonally and locally abundant prey and may migrate in response to seasonal prey fluctuations (Sigler et al 2009). The diets of both Steller and California sea lions, composed of a variety of bony and cartilaginous fishes and cephalopods, are often dominated by only a few species (Sinclair & Zeppelin 2002, Orr et al 2011, although as many as 25 different prey items have been found in a single scat (Riemer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The 'junk-food hypothesis' predicts neg-ative impacts on predators from reduced prey quality and was originally suggested as an explanation for the decline of Steller sea lion Eumetopias jubatus in the Gulf of Alaska (Alverson 1992). The hypothesis has been questioned, but is discussed as one of several likely mechanisms contributing to the lack of recovery in this population (Trites & Donnelly 2003, Fritz & Hinckley 2005, Sigler et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Eastern Bering Sea pollock fisheries would also be a possible candidate for integrating cooperative acoustic surveys and local management to mitigate hypothesized competitive interactions with northern fur seals (Callorhinus ursinus) [43] that could be a factor in its continued population decline [44]. There has been considerable research on nutritional requirements for both Steller sea lions and northern fur seals [30,[45][46][47] and the catch accounting system for bottom fish described for the Aleutian Islands [11] is similarly implemented in this fishery.…”
Section: Wider Implications and Applicationsmentioning
confidence: 99%